THE ECLIPSE HAS PASSED - Affandi , Nurfarahiyah Nasuha; Anand, L Alexis (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Primary adrenal insufficiency (PAI) can be misdiagnosed as other life-threatening conditions. Clinical signs of PAI are based on the deficiency of both glucocorticoids and mineralocorticoids. We report an infant with generalised hyperpigmentation and PAI. CASE A 10-month-old female, born via spontaneous vaginal delivery, with poor Apgar Score (1¹³⁵⁵¹⁰), was admitted for severe hypoxic-ischemic-injury (HIE). She had multiple episodes of seizures and required cooling therapy. Her parents are non-consanguineous. Clinically, she had generalised skin hyperpigmentation and normal female genitalia. She had severe metabolic acidosis (pH: 6.7, cHCO₃: 8.3 mmol/L, lactate: 14.1 mmol/L). She developed an adrenal crisis at day 5 of life with lowest sodium: 125 mmol/L (134–142) and highest potassium: >7 mmol/L (3.5–5.6). The lowest blood glucose was 3.2 mmol/L. Investigations at day 4 of life revealed low serum cortisol: 37.6 nmol/L (NV: 185–624), detectable testosterone: 0.9 nmol/L, normal 17-hydroxyprogesterone (17-OHP): 1.89 nmol/L (NV: <19.1), inappropriately low aldosterone: <103 pmol/L (NV: 471–4272) with high renin: >550 mU/L (NV: 4.00–89.00). The karyotype was 46 XX and the inborn error of metabolism study was non-diagnostic. Adrenocorticotropic hormone (ACTH) was normal at 5.16 pmol/L (NV: 1.60–13.90) but was done after initial doses of hydrocortisone. Pelvic ultrasonography (USG) showed Mullerian structures and cranial USG was normal. She was treated with stress dose of hydrocortisone 2.5 mg qid (45 mg/m²/day), then weaned to oral hydrocortisone 1.5 mg tid (16 mg/m²/day), fludrocortisone 150 mcg od and sodium chloride 0.5 grams bid. On follow-up, she had markedly reduced skin pigmentation. She had serum renin <1.80 mU/L and normal renal profiles. She was thriving with a weight of 7.4 kg (25–50th percentile), length of 65 cm (5–10th percentile) with appropriate developmental milestones. Our patient’s normal ACTH level was misleading due to hydrocortisone suppression. CONCLUSION Early diagnosis is crucial for effective management of PAI. Hyperpigmentation is a pathognomonic physical examination finding because ACTH shares the same affinity with α-melanocyte-stimulating hormone (MSH).